INDIGENOUS MEDICINAL PLANTS USED FOR TREATMENT OF DENGUE FEVER BY TRIBALS OF CHHATTISGARH (INDIA) - SMITA SAHU (International Journal of Pharma and Bio Sciences, 2015)
Dengue fever is the most prevalent mosquito transmitted viral infection affecting mortality and morbidity of billions of people across the world, specifically in the Tropics and sub-tropic regions, which has taken the Centre stage of tackling the dreaded diseases before the governments and the World Health Organization (WHO).Till now there is no particular approved vaccine or drug to counter the menace of the causative virus. As a consequence, the lookout for the new anti-dengue compounds from the indigenous medicinal plants has taken a great concern of necessity.The present paper deals with the indigenous medicinal plants used by the tribes of various regions of Chhattisgarh state for the treatment of Dengue fever. The tribals depend on the indigenous medicines for cure of surprisingly the dreaded Dengue fever. The herbal healers of these region use plant as a whole or the /plant parts of their suitable preparation as paste, powder, juice, decoction and extract for treating the ailment as per the Information collected from traditional tribal healers, baidya ,ojha, medicine men etc. Herbal healers and their patients who receive the treatment for the said ailment were enquired the local names, parts used and method of administration. Furthermore studies are suggested to validate the aforesaid claims to pave the path for herbal drug development for the treatment of such ailment.